2020
DOI: 10.1128/msphere.00393-20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Candida albicans Vaginal Isolates and a Laboratory Strain Show Divergent Behaviors during Macrophage Interactions

Abstract: Typically, established lab strains are widely used to study host-pathogen interactions. However, to better reflect the infection process, the experimental use of clinical isolates has come more into focus. Here, we analyzed the interaction of multiple vaginal isolates of the opportunistic fungal pathogen Candida albicans, the most common cause of vulvovaginal candidiasis in women, with key players of the host immune system: macrophages. We tested several strains isolated from asymptomatic or symptomatic women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Pathogenicity mechanisms of C. albicans are largely viewed through the lens of the reference isolate SC5314. However, intraspecies heterogeneity is highly relevant to strain-dependent pathogenicity and the virulence and fitness mechanisms employed by natural isolates is underappreciated [22,23,24]. One recent study demonstrated that despite all isolates retaining the PLOS PATHOGENS ECE1 variant contributes to reduced C. albicans virulence…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenicity mechanisms of C. albicans are largely viewed through the lens of the reference isolate SC5314. However, intraspecies heterogeneity is highly relevant to strain-dependent pathogenicity and the virulence and fitness mechanisms employed by natural isolates is underappreciated [22,23,24]. One recent study demonstrated that despite all isolates retaining the PLOS PATHOGENS ECE1 variant contributes to reduced C. albicans virulence…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of fungal macrophage cytotoxicity and survival were performed as previously described ( 69 ). Solely, the survival rates of AAP deletion strains were calculated relative to the wild type as follows: …”
Section: Methodsmentioning
confidence: 99%
“…The inability to clear fungal cells may therefore result in a situation in which polymorphonuclear cell recruitment is high and immunopathogenesis occurs as a consequence. Indeed, clinical isolates from the vaginal lumen display large amounts of variability in their basal levels of ß(1,3)-glucan exposure, and a correlation between increased fungal unmasking, neutrophil recruitment and symptom development for the patient has been established (Pericolini et al, 2018;Gerwien et al, 2020). Thus, unlike during systemic and oral infections, leveraging unmasking as a therapeutic approach for vulvovaginal candidiasis may have detrimental outcomes for the host.…”
Section: Relevance Of ß-Glucan Exposure To Pathogenesis and Disease C...mentioning
confidence: 99%